Positioning the #FeesMustFall Movement within the Transformative Agenda: Reflections on Student Protests in South Africa - Ntombana, Luvuyo; Gwala, Asemahle; Sibanda, Francis (Education as Change, 2023)
This article reflects on the successes and failures of student protests in transforming higher education in South Africa through a Marxist lens. The slow pace of change by the government in addressing structural and systemic inequalities has led to disgruntlement within the student body. In their quest to hasten the process, students engaged in protests across the country, inspired by the #RhodesMustFall movement. This article outlines the problematic areas that have led to the unrest and reflects on the #FeesMustFall movement: the lessons learnt and its impact on contemporary higher education. The reflection further unpacks what it means to be a student in South Africa and how the learning process shapes and is shaped by the student movements within universities. The study reviewed existing literature on the #FeesMustFall movement to better understand the influence of student protests on government policy and to evaluate whether any protest-based changes have occurred in higher education in South Africa.